2009
DOI: 10.1143/jjap.48.122301
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of Auger Electron Emission Features in Tip–Sample Electric Field Region for Scanning Probe Electron Energy Spectrometer

Abstract: A simulation study of the emission features of the Auger electrons in the electric field region localized within the cylindrical tip shield of a scanning probe electron energy spectrometer (SPEES) are reported. By taking into account synthetically the influence of every detailed factor, the relative intensity distributions for the outgoing Auger electrons are calculated by simulation. The results show that only those Auger electrons emitted from an annulus on sample surface with a width less than its radius ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Using this instrument, they compared the electron spectra obtained by a W (100) field-emission tip of STM with that by a conventional electron gun, and found that the high electric field introduced by the STM tip approaching near the surface would suppress the electron emitted from the sample surface and deform the measured spectra. This effect was confirmed and studied in the subsequent researches [3,[7][8][9]27], and a consensus was reached that the STM tip should be well shielded to obtain a quality electron spectrum by SPEES. A number of experiments were preformed to improve the shielding effect for the tip [4-8, 11, 24, 25, 28], and the most effective ones were achieved by Palmer's group [24] and our group [28] in different ways.…”
Section: Introductionmentioning
confidence: 59%
“…Using this instrument, they compared the electron spectra obtained by a W (100) field-emission tip of STM with that by a conventional electron gun, and found that the high electric field introduced by the STM tip approaching near the surface would suppress the electron emitted from the sample surface and deform the measured spectra. This effect was confirmed and studied in the subsequent researches [3,[7][8][9]27], and a consensus was reached that the STM tip should be well shielded to obtain a quality electron spectrum by SPEES. A number of experiments were preformed to improve the shielding effect for the tip [4-8, 11, 24, 25, 28], and the most effective ones were achieved by Palmer's group [24] and our group [28] in different ways.…”
Section: Introductionmentioning
confidence: 59%
“…However, early attempts to develop such an instrument encountered great difficulties, [10][11][12][13][14] mainly due to the strong electric field introduced by the tip bias, which greatly compresses the backscattered electrons and reduces the count rate. [15] Therefore, a novel electron energy analyzer with high detection efficiency is required.…”
Section: Introductionmentioning
confidence: 99%